PERSEPSI MAHASISWA CALON GURU DALAM PENGGUNAAN GAMIFIKASI PADA MATA KULIAH INOVASI PEMBELAJARAN BAHASA INDONESIA SD - Inggriyani, Feby; Sarah Anida Putri (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
Students are interested in learning if the learning process is fun are interested and enjoyable. In this Gen Z era, using games in learning is an effective way to attract attention and increase students' enthusiasm for learning. The purpose of this study was to examine the responses of PGSD students regarding the use of gamification in the Elementary School Indonesian Language Learning Innovation course in semester V. This research method is descriptive qualitative with triangulation data analysis techniques. Data collection was obtained from questionnaires, interviews, and observations. The results of the study showed that the use of gamification in the Elementary School Indonesian Language Learning Innovation course had a positive impact, and was able to create active, enjoyable learning, and motivated students. In addition, the gamification feature helps students understand the material better, facilitates access to the material, is fun, enjoyable, and challenging, increases enthusiasm, and interest in learning and learning outcomes, encourages them to create and use gamification, and recommends the use of gamification in Indonesian language learning in elementary school. Thus, this study can contribute to the development of more interesting and innovative learning.